Analysis of the Influence of Motors Installed in Passenger Car Wheels on the Torsion Beam of the Rear Axle Suspension - Piotr Dukalski; Bartłomiej Będkowski; Krzysztof Parczewski; Henryk Wnęk; Andrzej Urbaś; Krzysztof Augustynek (Energies, 2021)
The influence of mounting motors in wheels’ hubs and flexibility of the twist beam rear suspension on their dynamics and strength is presented in the paper. The international roughness indicator (IRI) is applied to assess the overcoming of road unevenness. This indicator is a combination of a shape of the road unevenness and of overcoming velocity. The movement of a wheel’s axis during obstacles overcoming is described. For the needs of the dynamics analysis, the mathematical model of the rear suspension system with embedded motors is developed using the MSC.Adams-ANSYS interface. The discrete model of the twist beam is prepared in the ANSYS software, which is used in the next step to construct the dynamics model of the rear suspension system using the MSC.Adams program. The vertical components of displacement and acceleration of the wheel’s centre, forces in the suspension’s springs and dampers, as well as forces in the joints are analyzed. The analysis of the suspension beam’s stress during the road unevenness overcoming is also carried out.